Treatment of patients with multiple myeloma who are not eligible for stem cell transplantation: position statement of the myeloma foundation of Australia Medical and Scientific Advisory Group. Issue 3 (March 2015) - Quach, H.; Joshua, D.; Ho, J.; Szer, J.; Spencer, A.; Harrison, S.; Mollee, P.; Roberts, A.; Horvath, N.; Talaulikar, D.; To, B.; Zannettino, A.; et al.
Abstract Options for treatment of elderly patients with multiple myeloma have expanded substantially following the development of immunomodulatory drugs (IMiD), proteasome inhibitors and with enhancement in safety of high‐dose therapy and autologous stem cell transplant (HDT + ASCT). The recognition of biological heterogeneity among elderly patients has made delivery of therapy more challenging. An individualised approach to treatment selection is recommended in an era in which highly efficacious treatment options are available for transplant‐ineligible patients. Here, we summarise recommendations for patients who are considered unsuitable for HDT + ASCT, including pretreatment considerations, and induction, maintenance and supportive care therapies.